Modelling the structural behaviour of rammed earth components - Silva, Rui André Martins (2014)
Proceedings of the Twelfth International Conference on Computational Structures Technology, B.H.V. Topping and P. Iványi, (Editors), Civil-Comp Press, Stirlingshire, Scotland.